2021
DOI: 10.1002/hbm.25434
|View full text |Cite
|
Sign up to set email alerts
|

Individual‐based morphological brain network organization and its association with autistic symptoms in young children with autism spectrum disorder

Abstract: Individual‐based morphological brain networks built from T1‐weighted magnetic resonance imaging (MRI) reflect synchronous maturation intensities between anatomical regions at the individual level. Autism spectrum disorder (ASD) is a socio‐cognitive and neurodevelopmental disorder with high neuroanatomical heterogeneity, but the specific patterns of morphological networks in ASD remain largely unexplored at the individual level. In this study, individual‐based morphological networks were constructed by using hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 92 publications
(112 reference statements)
0
10
0
Order By: Relevance
“…Farrant and Uddin found a hyperconnectivity of regions of interest in ASD children's attention network [ 66 ]. He et al used MRI and discovered that the morphological connectivity of the cortical-striatum-thalamus-cortical network of ASD increased and the morphological connectivity of the cortical-cortical network decreased [ 16 ]. In addition, several studies have shown that the working memory neural network and visual-motor neural network of ASD exhibit different FC patterns compared to a TD group [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farrant and Uddin found a hyperconnectivity of regions of interest in ASD children's attention network [ 66 ]. He et al used MRI and discovered that the morphological connectivity of the cortical-striatum-thalamus-cortical network of ASD increased and the morphological connectivity of the cortical-cortical network decreased [ 16 ]. In addition, several studies have shown that the working memory neural network and visual-motor neural network of ASD exhibit different FC patterns compared to a TD group [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Structural magnetic resonance imaging (sMRI) is a technique for examining the anatomical structure of the brain. Several sMRI studies have proved that there are structural abnormalities in the frontal lobe, temporal lobe, hippocampus, amygdala, and striatum of ASD subjects [11][12][13][14][15][16]. Functional neuroimaging of ASD brains mainly includes functional magnetic resonance imaging (fMRI), magnetic resonance spectroscopy (MRS), positron emission tomography (PET), single positron emission computed tomography (SPECT), diffusion tensor imaging (DTI), and functional near-infrared spectroscopy (fNIRS).…”
Section: Introductionmentioning
confidence: 99%
“…Structures identified include but are not limited to the temporo-parietal junction, prefrontal cortex, superior temporal gyrus, and amygdala (Kennedy & Adolphs, 2012). From a network perspective, in young children with ASC, grey matter covariance showed patterns of decreased connectivity in the cortex, that also predicted communication scores (He et al 2021). Nodal efficiency of tractography networks in infants who were later diagnosed with ASC was also found to be reduced in primary somatosensory, auditory and language areas (Lewis et al 2017), where changes were detected as early as six months and related to the level of autistic symptoms at 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of assembloids are being developed to investigate multi-synaptic circuitry in human models, such as cortico-thalamic, cortico-striatal, cortico-cortico assembloids ( Xiang et al, 2019 ; Andersen et al, 2020 ; Chen et al, 2020 ; Marton and Pasca, 2020 ). Cortico-thalamic and cortico-striatal dysfunction has been associated with neurodevelopmental disorders and associated co-morbidities such as epilepsy ( Shepherd, 2013 ; He et al, 2021 ). AUTS2 is highly expressed in the dorsal thalamus and in the striatum ( Bedogni et al, 2010 ), to study neural circuitry between the frontal cortex and these brain regions.…”
Section: Generation Of Brain Region-specific Cerebral Organoids and A...mentioning
confidence: 99%